Reading Text for School Literacy Movement in Mathematics Learning - Kiki Nia Sania Effendi; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Poppy Yaniawati (Jurnal Pendidikan Matematika, 2020)
This article discusses the results of the reading text development on the small group stage for reading activities on the school literacy movements in mathematics learning with the futsal game context, which is currently being enjoyed by the people, especially among students. This research used a design research method whose type is development studies. The evaluation flow at the prototyping stage uses the formative study flow with the stages of self-evaluation, expert review and one-to-one, small group, and field test. The research subjects were 7th-grade students in one of the junior high schools in Kabupaten Karawang. Documentation, questionnaires, and interviews are ways to collect data in this study. This study has produced the reading texts that are used for the school literacy movement program with the futsal context on practical mathematics learning.